130 Focusing With a New Lens: Analyzing the Quality of Internet Literature Related to the Gut Microbiome - Clarke, Lindsay; Baumgartner, Scott; Szvarca, Daniel; Tabbara, Nadeem; Basso, Jessica; Dawit, Lillian; Dave, Jenny; Borum, Marie (The American journal of gastroenterology, 2019)
INTRODUCTION:The study of intestinal microbiota and its potential impact on human disease is an emerging field of research. Investigations initially focused on gastrointestinal disorders, but have expanded to include issues related to metabolic, immune, and neurologic function. Since individuals increasingly use electronic resources for medical decisions, assessment of available information is important. This study evaluated the readability, quality and use of evidence-based support of readily accessible online information about intestinal microbiota.METHODS:The search terms “gut microbiome” were inputted into Google. Exclusion criteria included websites that were non-accessible, included videos without transcripts, provided veterinary information or were duplicates. Sites were categorized by intended audience, either patient or professional. Readability was determined using the validated Flesch-Kincaid Grade Level Calculation. Websites were reviewed for inclusion of references, provision of additional links for further reading, and the acknowledgement of areas of uncertainty. Statistical analysis using a two-tailed Fisher's Exact Test and a Two-Sample T-test were used with a P-value set at < 0.05.RESULTS:100 websites were assessed with 87 meeting criteria for inclusion. 46 (52.9%) were intended for patients and 41 (47.1%) were for medical professionals. The average Flesch-Kincaid Grade level was 14.1, with significant difference (P < 0.0001) between patient (12.6 grade level) and professional (15.8 grade level) websites. 58.6% (25 patient; 26 professional) of websites provided additional links for further information. While 36.7% (12 patient, 20 professional) of all websites acknowledged areas of uncertainty, patient websites significantly more often (P = 0.04) acknowledged areas of uncertainty compared to professional. Patient sources were significantly (P < 0.0001) less likely to provide references (34.7%) as compared to non-patient sources (87.8%).CONCLUSION:Online resources on gut microbiome are readily accessible for patient and professional audiences. However, the readability of patient information exceeded the NIH 6th grade recommended reading level. Additionally resources infrequently provided references, links for additional information or acknowledged areas of uncertainty. As the gut microbiome becomes increasingly studied, it is critical that online information be readable and supported by evidence based research.